The Impact of News about Pandemic on Borsa Istanbul during the COVID-19 Financial Turmoil - Ömer Faruk Tan (Türkiye İletişim Araştırmaları Dergisi)
The COVID-19 pandemic, which emerged in December 2019 and then spread worldwide, has affectednot only economic and social life but also the financial markets. It has left investors greatly panickedand affected their decisions. In this study, the effect of COVID-19 related news on Borsa Istanbulis analyzed using the panel quantile regression method. The study period is set between 10 March2020 and 17 April 2020. The panic index, media hype index, fake news index, country sentimentindex, infodemic index, and media coverage index created by the RavenPack data platform are usedfor the analysis. The impact of news, it was found, varies amongst the quantiles, and there exists anasymmetric dependence between the returns of Borsa Istanbul and COVID-19 related news. Moreefficient communication channels, the results indicate, should be used to alleviate the financial turmoilcaused by COVID-19.